Impact of the COVID-19 Pandemic on the Welfare of Animals in Australia - Baptista, Jacqueline; Blache, Dominique; Cox-Witton, Keren; Craddock, Nicola; Dalziel, Toni; de Graaff, Nicolas; Fernandes, Jill; Green, Ronda; Jenkins, Helen; Kahn, Sarah; Kelly, Deborah; Lauber, Mariko; et al. (Frontiers in Veterinary Science, 2021)
We report on the impact of the COVID-19 pandemic of 2020 on the welfare of animals under the care of various sectors in Australia. Most organisations and individuals with animals under their care had emergency preparedness plans in place for various scenarios; however, the restrictions on human movement to contain the spread of COVID-19, coupled with the economic impact and the health effects of COVID-19 on the skilled workforce, constituted a new threat to animal welfare for which there was no blueprint. The spontaneous formation of a national, multisectoral response group on animal welfare facilitated information flow during the crisis, which helped to mitigate some of the shocks to different sectors and to ensure continuity of care for animals during the pandemic. We conclude that animal welfare is a shared responsibility, and accordingly, a multisectoral approach to animal welfare during a crisis is required. Our experience demonstrates the need for clear communication channels to safeguard animal welfare during crises. Our findings and recommendations from the Australian context may inform other countries to ensure that animal welfare is not compromised in the course of unpredictable events.